2022
DOI: 10.32604/iasc.2022.023252
|View full text |Cite
|
Sign up to set email alerts
|

Forward Flight Performance Analysis of Supercritical Airfoil in Helicopter Main Rotor

Abstract: In this research, the aerodynamic performance and flow characteristics of NASA SC (2)-0714 airfoil and HH02 airfoil in the helicopter main rotor are evidently analyzed. The supercritical airfoil is used in the aircraft for attaining better transonic and high-speed flow characteristics. Moreover, a specialized helicopter airfoil called HH02 is used in the Apache helicopter rotor for increasing the operational speed. As most of the high-speed helicopters are using four-bladed main rotor configuration, it is anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Catia V5 is used in this research work to design the three-bladed and four-bladed helicopter blades. e same model is used for the experimental model and scaled down for wind tunnel size using the 3D printing method [19,20]. e designed model will be imported to fluent for further analysis.…”
Section: Design and Preprocessingmentioning
confidence: 99%
“…Catia V5 is used in this research work to design the three-bladed and four-bladed helicopter blades. e same model is used for the experimental model and scaled down for wind tunnel size using the 3D printing method [19,20]. e designed model will be imported to fluent for further analysis.…”
Section: Design and Preprocessingmentioning
confidence: 99%
“…And unstructured meshing can also be used for wing (3D) analysis [19]. There is a lot of evidence for the increment in the lift with respect to the high angle of attack, and flow over an airfoil separates when the velocity of the flow around the airfoil is less [20]. To do the computational analysis for the nozzles, Ansys Fluent and CFD solvers are used, and K-ε model, K-omega, and Spalart Allmaras model are used as turbulence models [21].…”
Section: Review Of Literature and Theorymentioning
confidence: 99%
“…Using the k-ω model in the interior parts of the boundary layer causes the model to use directly down to the wall through the viscous sublayer, so the shear stress transport (SST) k-ω model can be used as a low Reynolds turbulence model without any additional damping functions. The SST modal also changes to a k-epsilon (ε) behaviour in the free stream[20,21,25]. Therefore, it avoids the general k-ω problem that the model is highly sensitive to the inlet turbulence properties of the free stream.…”
mentioning
confidence: 99%
“…Wang (Wang et al , 2023) and Li (Li et al , 2021) conducted a study of the dynamic stall of the S809 airfoil in a sandy environment. Hasan (Hasan et al , 2022b; Hasan and P, 2022a) studied the influence of supercritical airfoil on helicopter characteristics and found that supercritical airfoil can increase efficiency and produce good aerodynamic characteristics. Liu (Liu et al , 2023) analysed the effect of sandy flow with a low Reynolds number in transonic flow on the aerodynamic performance of an airfoil of a Mars UAV.…”
Section: Introductionmentioning
confidence: 99%